Student satisfaction in e-learning along the COVID-19 pandemic with importance performance analysis - Lila Bismala; Yayuk Hayulina Manurung (International Journal of Evaluation and Research in Education (IJERE), 2021)
The COVID-19 pandemic caused learning to be done with an online system, one of which is by using e-learning. The use of e-learning received a lot of reactions, both from the student and lecturer side. Lecturers should be able to make the best preparation, both in terms of materials, media, content, interaction and flexibility in the use of e-learning, so that students do not have difficulty in distance learning done. While students should prepare themselves as best as possible, both in terms of technology, ability, interaction with colleagues and lecturers, as well as motivation in conducting distance learning using e-learning. This study aimed to investigate student satisfaction in using e-learning as a method of distance learning during the COVID-19 pandemic, using Importance Performance Analysis (IPA). The number of respondents in this study was 132 students. The results showed that there are several factors that need to be improved, such as materials presented in e-learning, interaction with lecturers, availability of facilities, and lecturers. Factors that should be maintained included flexibility, assessment in e-learning that is felt to be appropriate, the benefits of e-learning, and students' ability to allocate time. Meanwhile, factors that are considered less important and do not obtain priorities include peers, easy-to-understand materials, ability to learn independently and understand tasks. In addition, students consider there are several factors that are considered too excessive, namely self-motivation, ability to understand the use of e-learning, independent learning process.